Tratamiento informativo realizado por diario El Comercio sobre la crisis carcelaria de Ecuador, período junio – noviembre 2021 - Velásquez Lozano, Luis Fernando (2024)
ABSTRACT: The present research focused on investigating and analyzing the information treatment carried out by the newspaper El Comercio on the prison crisis in Ecuador from June to November 2021. This work was qualitative and quantitative, with the news published on the website as a variable of the media, based on functionalist theory and information theory. The scientific, descriptive, and analytical methods are used to determine the main objectives of this research. In addition to several techniques, content analysis and interviews had instruments that will help deepen and detail the information, such as a qualitative-quantitative content analysis matrix, a general data sheet of qualitative-quantitative content analysis, and a guide to the interview. One hundred and two news items that El Comercio published during June – November 2021 were analyzed. , a matrix was worked on to collect data, which was made up of section categories, journalistic genre, location, sources, graphic aid element (quantitative), what is said about the news (qualitative), plus an analysis and interpretation of the data produced by this first technique. For greater complementation of the information, interviews with two experts were also used that covered both variables: informative treatment: a journalist; prison crisis: an official of some public entity related to this crisis, for example, the SNAI. Keywords: El Comercio, media, information treatment, prison crisis, Ecuador.